2006
DOI: 10.1136/jcp.2005.029744
|View full text |Cite
|
Sign up to set email alerts
|

Twenty year review of histopathological findings in enucleated/eviscerated eyes

Abstract: Background/Aims: To evaluate the need for routine histopathological analysis of enucleated/eviscerated eyes and changes in indications for eye removal. Methods: Retrospective review of all enucleation/evisceration histopathology reports over 20 years. Clinical history was correlated with pathological findings. Two 10 year periods (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003) were compared to detect changes in indications for eye removal. Results: In total, 285 histopathology results were traced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
2
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 5 publications
3
22
2
5
Order By: Relevance
“…In the United Kingdom, for the period from 1994 to 2003, Saeed et al reported a sequence of causes for ocular enucleations starting with ocular trauma, followed by phthisis bulbi and endophthalmitis. 8 Although in the present study, the sequence of clinical indications for ocular enucleation was similar to the findings of de Gottrau and Naumann from Germany, 1,2 with trauma (37.4%), malignant intraocular tumours (19.6%), systemic diseases (17.1%), surgical complications (14.1%), and intraocular infection and inflammation (7%) in the list, the proportion of ocular trauma (62.5%) and malignant intraocular tumours (28.5%) were higher in the present study. In the latter study, the reasons for ocular enucleations owing to ocular traumata might have slightly shifted from surgical difficulties in salvaging the eye and pain alleviation to eventually cosmetic reasons to remove the deformed eye.…”
Section: Indications and Aetiologies Distributionmentioning
confidence: 99%
“…In the United Kingdom, for the period from 1994 to 2003, Saeed et al reported a sequence of causes for ocular enucleations starting with ocular trauma, followed by phthisis bulbi and endophthalmitis. 8 Although in the present study, the sequence of clinical indications for ocular enucleation was similar to the findings of de Gottrau and Naumann from Germany, 1,2 with trauma (37.4%), malignant intraocular tumours (19.6%), systemic diseases (17.1%), surgical complications (14.1%), and intraocular infection and inflammation (7%) in the list, the proportion of ocular trauma (62.5%) and malignant intraocular tumours (28.5%) were higher in the present study. In the latter study, the reasons for ocular enucleations owing to ocular traumata might have slightly shifted from surgical difficulties in salvaging the eye and pain alleviation to eventually cosmetic reasons to remove the deformed eye.…”
Section: Indications and Aetiologies Distributionmentioning
confidence: 99%
“…As principais etiologias que desencadearam a retirada do globo ocular foram trauma ocular, glaucoma, melanoma de coróide e phthisis bulbi. Não obstante, este resultado foi semelhante ao encontrado em outros estudos (10,12,14,15) ; embora a endoftalmite, em alguns destes estudos, tenha se destacado dentre as principais complicações, fato não sucedido neste trabalho.…”
Section: Discussionunclassified
“…A alta frequência do trauma ocular é vista em vários estudos (5,8,13,14,16) , segundo um estudo em Bogotá (Colômbia), onde dos 370 pacientes submetidos à cirurgia de enucleação ou evisceração, 49,19% revelaram como etiologia o traumatismo ocular (17) . Há também um trabalho em que foram analisados 890 casos de enucleação durante um período de 22 anos, onde 39,7% dos casos corresponderam ao trauma ocular (18) .…”
Section: Discussionunclassified
“…Entretanto, para além da função de percepção, os olhos representam um importante fator psicodinâmico, pela sua grande influência no relacionamento social (6) . Sendo assim, em decorrência dos avanços tecnológicos e científicos no campo da oftalmologia, a remoção do globo ocular tem-se tornado cada vez menos freqüente, sendo indicado apenas quando todas as possibilidades de manutenção do olho forem esgotadas, visto ser este um procedimento dos mais traumatizantes (13) .…”
Section: Discussionunclassified
“…Tais fatos levam à necessidade de apoio e encorajamento e, sendo assim, um tratamento personalizado pode ser oportuno (5) . Dessa forma, é importante a atuação multiprofissional e interdisciplinar, visando oferecer a melhor reabilitação possível ao indivíduo afetado, de forma a minimizar o impacto que esta condição propicia (6) . Com relação à etiologia da perda do globo ocular verificase variação na literatura científica.…”
Section: Resumo Introduçãounclassified